Pediatric Rheumatology - Ravelli, Angelo; Avcin, Tadej; Spencer, Charles T.; Martini, Alberto; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Pediatric Rheumatology is the official publication of the Pediatric Rheumatology European Society (PReS). Submissions on the evaluation and treatment of non-surgical musculoskeletal syndromes and diseases in children and adolescents, particularly autoimmune and rheumatic diseases are welcomed. Diseases and syndromes of particular interest include musculoskeletal pain syndromes, rheumatic fever and post-streptococcal syndromes, juvenile idiopathic arthritis, systemic lupus erythematosus, juvenile dermatomyositis, local and systemic scleroderma, Kawasaki disease, Henoch-Schonlein purpura and other vasculitides, sarcoidosis, inherited musculoskeletal syndromes, autoinflammatory syndromes, and others. Pediatric Rheumatology encourages submissions on educational advances, drug studies, laboratory and radiological evaluations, and outcome measures.
Keywords: Pediatrics; Rheumatology; Pediatrics; Rheumatology